Nilaparvata lugens salivary protein NlG14 triggers defense response in plants. (3rd September 2022) - Gao, Haoli; Zou, Jianzheng; Lin, Xumin; Zhang, Huihui; Yu, Na; Liu, Zewen
Abstract: The brown planthopper (BPH), Nilaparvata lugens (Stål) (Hemiptera: Delphacidae), is a serious insect pest on rice. It uses its stylet to collect sap by penetrating the phloem and at the same time it delivers saliva into the host plant, which can trigger a reaction. The molecular mechanisms by which BPH salivary proteins result in plant responses are poorly understood. In this study, we screened transcriptomic data from different BPH tissues and found a protein specific to the salivary gland, NlG14, that could induce cell death in plants. We determined that NlG14 is uniquely found in the insect family Delphacidae. Detailed examination of N. lugens showed that NlG14 was mainly localized in the A-follicle of the principal gland of the salivary gland, and that it was secreted into rice plants during feeding. Knockdown of NlG14 resulted in significant nymph mortality when BPH was fed on either rice plants or on an artificial diet. Further analysis showed that NlG14 triggered accumulation of reactive oxygen species, cell death, callose deposition, and activation of jasmonic acid signaling pathways in plants. Transient expression of NlG14 in Nicotiana benthamiana decreased insect feeding and suppressed plant pathogen infection. Thus, NlG14, an essential salivary protein of N. lugens, acted as a potential herbivore-associated molecular pattern to enhance plant resistance to both insects and plant pathogens by inducing multiple plant defense responses. Our findings provide new insights into the molecular mechanisms of insect–plant interactions and offer a potential target for pest management. Abstract : A salivary protein, NlG14, from Nilaparvata lugens is secreted into rice during feeding and induces multiple defense responses that enhance plant resistance to both insects and fungal pathogens.